The Association Between Sexism, Self-Sexualization, and the Evaluation of Sexy Photos on Instagram - Plieger, Thomas; Groote, Olivia; Hensky, Rachel; Hurtenbach, Lea; Sahler, Sharon; Thönes, Luise; Reuter, Martin (Frontiers in Psychology, 2021)
Passive consumption of sexually objectifying content on Social Networking Sites (SNS) has been shown to result in lowered body satisfaction and self-esteem particularly in women. However, deliberate evaluations of sexually objectifying social media content are scarce. Furthermore, associations between self-objectification and active use of SNS in terms of posting behavior haven’t been shown so far. The present study asked N=916 participants to rate 28 Instagram screenshots on three dimensions, namely whether the given photos were perceived as sexually revealing, appropriate, and attractive. The ratings were related to sexist attitudes, enjoyment of sexualization and participants’ posting behavior. Sexism was negatively associated with perceived appropriateness of the presented Instagram photos in women. Furthermore, there were substantial correlations between appropriateness and attractiveness evaluations of the presented photos and female users’ own self-sexualizing posting behavior as well as their enjoyment of sexualization. Only inconsistent effects could be found in men. Greater appreciation of objectification seems to go along with self-objectifying behavior, which may be due to an altered perception of what can be considered as sexually revealing. Although effects seem to be smaller in men, future research should also focus on male enjoyment of sexualization, which unfortunately was not considered in the present study.